Massage As complementary therapy in Children with Acute Diarrhea: A Case Study - Arbianingsih; Huriati; Fauziah Nur (Nursing Practice Journal, 2026)
Acute diarrhea in children is a significant health problem in developing countries that contributes significantly to child morbidity and mortality. A complementary approach, massage therapy, has the potential to support the patient's recovery optimally. This study aims to explain the application of massage therapy in nursing interventions for children with acute diarrhea and evaluate its impact on the frequency of defecation and intestinal peristalsis. The research employed a case study design on a hospitalized 11-month-old child diagnosed with acute diarrhea. Interventions included diarrhea management, nutrition management, and abdominal massage therapy twice a day for three days. The results showed a decrease in the frequency of defecation from five times to once per day, a stabilized frequency of intestinal peristalsis at five times per minute, and an improvement in general condition. The mechanism of action of massage involves an increase in vagal activity, modification of the intestinal microbiota, and a reduction in stress hormones, all of which have a positive impact on gastrointestinal function. Massage therapy has been proven to be safe, effective, and easily integrated into pediatric nursing. Massage therapy can be utilized as an evidence-based complementary intervention for managing acute diarrhea in children with defecation frequency decreased from 5 per day to one per day and peristalsis stabilized at 5 per minute. Massage therapy has potential positive implications for enhancing the quality of nursing care in the pediatrics area.